Inovasi Pertanian Menuju Kemandirian Pangan Masyarakat Kabupaten Malaka - Berek, Dominikus Isak Petrus; Manek, Marianus (Journal of Innovation in Management, Accounting and Business, 2024)
This research aims to investigate the impact and implications of the agricultural revolution on food self-sufficiency in Kabupaten Malaka. As an agrarian region, Kabupaten Malaka faces significant challenges in achieving food self-sufficiency. The revolution gave birth to innovations in community farming practices. This research uses qualitative methods with data collection techniques through in-depth interviews, field observations and document analysis. The research approach used was extemporaneous phenomenology. The results show that the implementation of the agricultural innovations has had a significant impact on increasing local food production and reducing dependence on food imports. However, there are still some obstacles that need to be overcome, such as access to agricultural technology, climate change and lack of stable market access. The study concludes that the agricultural revolution has made a significant contribution to food self-sufficiency in Kabupaten Malaka, but greater efforts are needed to overcome the remaining challenges